2006
DOI: 10.1159/000090423
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Oral Slow Release Morphine for Maintenance Treatment in Heroin Addicts: A 6-Month Open Noncomparative Study

Abstract: This open-label, noncomparative, single-center trial evaluated the safety and efficacy of once-daily treatment with slow release oral morphine (SROM) capsules for the maintenance treatment of 20 outpatients with heroin dependency over 6 months at the National Institute for Addictions in Sofia, Bulgaria. Doses were individually titrated up to a mean daily maintenance dose of 760 mg (range 440–1,200 mg). SROM was effective in significantly reducing the signs and symptoms of opioid withdrawal and craving for hero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 33 publications
(21 reference statements)
3
13
0
Order By: Relevance
“…These results strongly support previous findings of increased QoL for patients in maintenance treatment compared with patients at admission or those seeking treatment [22,35,43,44] .…”
Section: Discussionsupporting
confidence: 91%
“…These results strongly support previous findings of increased QoL for patients in maintenance treatment compared with patients at admission or those seeking treatment [22,35,43,44] .…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, SROM is a promising compound that is complementary to existing substances for maintenance treatment and has been authorized for maintenance treatment of opioid dependence in a few European countries. Several smaller and mostly open-label studies have shown positive results for SROM with respect to retention, reduced heroin use, and (or) improved quality of life (135)(136)(137)(138)(139). Further studies will have to confirm these results before the added value of this substance for the treatment of heroin dependence can be established.…”
Section: Maintenance Treatmentmentioning
confidence: 96%
“…Given the high prevalence rates of psychiatric comorbidity in opioid-dependent patients, the effects of substitution medication on these symptoms in particular are of special interest [11]. Previous studies suggest positive effects of slow-release oral morphine on depression, anxiety or quality of life [9,10,12]. However, only the study of Eder et al [9] had a controlled design, and it failed to show superior quality of life results for slow-release oral morphine compared to methadone [13].…”
Section: Introductionmentioning
confidence: 99%